THE IMPACT OF PREOPERATIVE STEROIDS ADMINISTRATION ON ENDOSCOPIC SINUS SURGERY: A COMPREHENSIVE SYSTEMATIC REVIEW - Agung Nugroho, Satya; Habib Afifudin, Hasnan; Rachman , Rury Annida; Handriono, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Chronic rhinosinusitis (CRS) is one of the most common diseases in the world, affecting approximately 14 of people in the USA. It is defined as chronic inflammation of nasal and sinus cavities lasting longer than 12 weeks, it can be with or without nasal polyposis (CRSwNP or CRSsNP), primary and secondary, localized or diffuse disease regarding anatomic distribution, either type 2 or non-type 2, considering the endotype dominance, eCRS, and non-eCRS for eosinophilic and non-eosinophilic CRS. The aim: This study aims to show about the impact of preoperative steroids administration on endoscopic sinus surgery. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 51 articles, whereas the results of our search on SagePub brought up 74 articles. The results of the search conducted for the last year of 2014 yielded a total 24 articles for PubMed and 48 articles for SagePub. The result from title screening, a total 5 articles for PubMed and 12 articles for SagePub. In the end, we compiled a total of 8 papers. We included five research that met the criteria. Conclusion: Low dose preoperative systemic steroid (PSS) does not seem to have an effect on the long term outcome after endoscopic sinus surgery (ESS) in chronic rhinosinusitis (CRS) with nasal polyposis (NP). Eosinophilic infiltration and presence of asthma are important predictors of surgical outcome in such cases.